2018
DOI: 10.1007/s13167-018-0133-y
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes care in figures: current pitfalls and future scenario

Abstract: Diabetes mellitus (DM) epidemic-on a global scale-is a major and snowballing threat to public health, healthcare systems and economy, due to the cascade of pathologies triggered in a long-term manner after the DM manifestation. There are remarkable differences in the geographic disease spread and acceleration of an increasing DM prevalence recorded. Specifically, the highest initial prevalence of DM was recorded in the Eastern-Mediterranean region in 1980 followed by the highest acceleration of the epidemic ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 16 publications
(18 reference statements)
1
52
0
Order By: Relevance
“…While multiple factors are likely to be responsible for these trends, clarity of treatment guidelines, and the quality of patient care are undoubtedly important factors for consideration. To this end, Owolabi et al found that the majority of national guidelines from low-and middle-income countries were inadequate in terms of applicability, clarity, and dissemination plan and not adequately contextualized for socioeconomic status as compared to highincome countries [196]. The introduction of practical and enforceable national guidelines would likely improve clinical outcomes and narrow the mortality gaps observed between countries of different economic status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While multiple factors are likely to be responsible for these trends, clarity of treatment guidelines, and the quality of patient care are undoubtedly important factors for consideration. To this end, Owolabi et al found that the majority of national guidelines from low-and middle-income countries were inadequate in terms of applicability, clarity, and dissemination plan and not adequately contextualized for socioeconomic status as compared to highincome countries [196]. The introduction of practical and enforceable national guidelines would likely improve clinical outcomes and narrow the mortality gaps observed between countries of different economic status.…”
Section: Discussionmentioning
confidence: 99%
“…Affordable and cost effective medications such as the sulfonylureas provide a rational approach to treatment of T2D in EMG countries, deterring cost without compromising outcome [195]. Additionally, innovative digital healthcare and approaches advocating predictive, preventive, and personalized medicine should be explored as future tools to harmonize diabetes care and reduce the cost burden in all markets considered [196].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus (DM) is an increasingly common disease with a prevalence of almost 500 million people worldwide and DM is directly responsible for 1.6 million deaths per year [ 1 , 2 ]. It is expected that these high numbers will keep increasing over the coming decades if no effective preventive strategies are implemented [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus (DM) is an increasingly common disease with a prevalence of almost 500 million people worldwide and DM is directly responsible for 1.6 million deaths per year [ 1 , 2 ]. It is expected that these high numbers will keep increasing over the coming decades if no effective preventive strategies are implemented [ 1 ]. An important part of these deaths and the morbidity associated with DM are caused by arterial thrombotic disorders, such as myocardial infarction or stroke [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Operational implementation of PPPM perceptions to diabetes mellitus (DM) care is due long ago. The European Association for Predictive, Preventive and Personalised Medicine (EPMA) emphasizes the need to debate the large-scale complex approach for diabetes care, especially those with comorbid pathologies such as cardiovascular disease (CVD), cancer, and neurological, neuropsychiatric, and neurodegenerative diseases (NNND) [1,19,20].…”
Section: Diabetes Mellitus: It Is Not All About the Insulinmentioning
confidence: 99%